Innovative Approach For Professional Development For Language Teachers In The Digital Age - Nurfidah Nurfidah; Supriadin Supriadin; Evi Rosdiyanti; A. Fandir (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The development of digital technology has brought significant changes to language learning practices and requires language educators to continuously improve their professional competencies through innovative approaches. This study aims to examine various innovative approaches to the professional development of language educators in the digital era and identify their benefits, challenges, and implications for improving the quality of language learning. The study employed a qualitative descriptive approach through literature review and limited case studies. Data were collected through analysis of reputable scientific documents, education policy reports, and semi-structured interviews with language educators and professional development program managers. Data analysis was conducted thematically to identify patterns, strategies, and barriers in the implementation of innovative technology-based approaches. The results show that innovative approaches, such as digital technology integration, collaborative learning, and strengthening digital literacy, contribute positively to improving the pedagogical, professional, and digital competencies of language educators. However, challenges such as limited technological skills and resistance to change remain major obstacles. These findings emphasize the importance of developing professional development models that are contextual, sustainable, and adaptive to the dynamics of language education in the digital era.